(untitled) (ARQUISUR Revista, 2011)
In the context of a new ideological framework, this article reflects upon an updating of the «Plan de Ordenamiento Territorial de Montevideo» since it was approved in 1998, by proposing six challenges for the revision of the current Planning Principles. These challenges try to link the world of theory and practice, by suggesting innovative concepts to be taken in consideration and at the same time, proposing tools and methods to put them in practice. In effect, Peter Hall, acclaimed author of urban theories in the last four decades, recognises a divorce between the academic research and the planning in practice. Bringing both worlds closer is possibly the main challenge in between.